Effort and reward as a mechanism linking leader-member exchange with work engagement - Tanskanen, Jussi (Taylor & Francis, 2024)
Leader-member exchange (LMX) theory consentrates on the unique dyadic relationships between leaders and followers. Consistent evidence associates LMX relationships to employee work engagement, but research on the mechanisms explaining the connection has remain scarce. This study applies social exchange, LMX and effort-reward imbalance theories to examine whether the effort made by employee and the reward gained mediate the relationship between LMX and three dimensions of work engagement: vigor, dedication, and absorption. A large Finnish cross-sectional sample (M = 1701) collected from service-sector was analysed utilizing path modelling. The results indicate that high-quality LMX relationships were connected with employees’ greater reward and reduced effort, which in turn partially mediated the positive association to work engagement dimensions. Reward was positively connected with vigor, dedication, and absorption, while effort had a negative relationship with vigor and a positive association with absorption. There was no significant interaction effect between effort and reward on any work engagement dimension. This study contributes to literature by connecting LMX with work engagement dimensions and, more importantly, provides empirical evidence on the mechanism explaining these relationships. Reward had a particularly important role in explaining the relationships. Distinct associations with vigor, dedication and absorption encourages to examine them separately in future studies.
Keywords: leader-member exchange(lMX); effort; reward; effort-reward imbalance (eRi) model; work engagement; fi=Henkilöstöjohtaminen|en=Human Resource Management|